Understanding Communication Effectiveness, Communication Satisfaction, Self-Efficacy, and Self-Care Management Among Patients With Chronic Disease. Issue 2 (April 2019) - Kashian, Nicole; Mirzaei, Tala
This study investigates channel choice and effective patient-provider communication, patient satisfaction, self-efficacy, and self-care management among patients with a chronic disease by applying and testing two prominent media choice theories: channel expansion theory and media synchronicity theory. A national sample of respondents with chronic disease completed measures assessing constructs from each theory. The model for media synchronicity theory provided a better fit for the data than did the model for channel expansion theory. By providing an integrative model of effective patient-provider communication, this research provides practitioners and patients with theoretically -based empirical guidance to advance the study of chronic disease management.